(untitled) (Research, Society and Development, 2020)
Due to the complexity of the physiological effects in fruit ripening stages, characterizing volatile compounds helps to decipher changes in color, aroma, firmness, flavor and texture. Solid phase microextraction (SPME) can prevent heating and prevent the degradation of aromatic compounds, and therefore has been widely used for the extraction and enrichment of aromatic components, including those from fruits. In this context, the objective of this work was to verify the volatile compounds during the ripening process of starfruit (Averrhoa carambola) and seriguela (Spondias purpúrea L.) using the solid phase microextraction (SPME) technique coupled to gas chromatography-spectrometry of mass (GC-MS). It was possible, using the SPME / CG-MS technique, to identify the volatile composition of the star fruit and seriguela at different stages of maturity. In both fruits compounds were observed that can be used as markers of the maturation stage. The aroma of carambola was made up mainly of esters and that of seriguela, mostly aldehydes and esters.